PENGEMBANGAN ELEKTRONIK LEMBAR KERJA PESERTA DIDIK (E-LKPD) INTERAKTIF MENGGUNAKAN WIZER.ME PADA PEMBELAJARAN IPS - Firly Annisa' Zein; Musyarofah Musyarofah (Prima Magistra: Jurnal Ilmiah Kependidikan, 2024)
This research has a background, namely teachers in making E-LKPD is still limited to the form of multiple-choice questions and essays. Electronic student worksheets (E-LKPD) are also directly components on doing questions or answering questions. E-LKPD uses this Wizer.me platform has never been used by teachers in social studies learning and also wants to develop other interesting technologies such as this Wizer.me which has a variety of question forms such as drawing, filling in clumped sentences, and so on, and this can generate student interest in social studies. The purpose of this study is to determine the validity and effectiveness of Interactive E-LKPD using Wizer.me in social studies learning Community Life Material During the Hindu-Buddhist Period grade VII SMP Negeri 1 Panti for the 2022/2023 academic year. This research uses research and development methods. The research model used is ASSURE. The data obtained is in the form of qualitative and quantitative data. Data collection techniques used include interviews, documentation, and questionnaires. This research has the following results: 1) The results of the validity test conducted by material experts obtained a percentage of 76% which means quite valid, media / design experts obtained a percentage of 87% which means very valid, and linguists obtained a percentage of 87% which means very valid. Of the three results, an average percentage of 83% was obtained with a fairly valid category. 2) The results of the effectiveness of E-LKPD tested on students get a percentage of 87% which is categorized as very effective.